2023
DOI: 10.21037/atm-23-276
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ferroptosis-related genes in ulcerative colitis: a diagnostic model with machine learning

Abstract: Background: Ulcerative colitis (UC) is an idiopathic, chronic disorder characterized by inflammation, injury, and disruption of the colonic mucosa. However, there are still many difficulties in the diagnosis and differential diagnosis of UC. An increasing amount of research has shown a connection between ferroptosis and the etiology of UC. Therefore, our study aimed to identify the key genes related to ferroptosis in UC to provide new ideas for diagnosis UC.Methods: Gene expression profiles of normal and UC sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Similarly, ferroptosis genes such as ACSL4, GPX4, and glucose 6 phosphate dehydrogenase are either up-or downregulated in specimens of patients with UC [343]. Moreover, five ferroptosis-related hub genes were identified that can discriminate UC patients from healthy individuals [344].…”
Section: Ferroptosis In Ibdmentioning
confidence: 99%
“…Similarly, ferroptosis genes such as ACSL4, GPX4, and glucose 6 phosphate dehydrogenase are either up-or downregulated in specimens of patients with UC [343]. Moreover, five ferroptosis-related hub genes were identified that can discriminate UC patients from healthy individuals [344].…”
Section: Ferroptosis In Ibdmentioning
confidence: 99%
“…Qian et al [ 33 ] identified five ferroptosis-related hub genes ( LCN2 , MUC1 , PARP8 , PLIN2 , TIMP1 ) and built a high-performing logistic regression model to diagnose UC. Bu et al [ 34 ] found four potential UC biomarkers ( HSPB3 , ABCG2 , VNN1 , SLC6A14 ) confirmed in an independent dataset (AUC = 0.889).…”
Section: Review Of Literaturementioning
confidence: 99%